Immune Contexture Changes Following Blue Light Cystoscopy with Hexaminolevulinate in Bladder Cancer - Sara Kaczor Elbæk; Tine Ginnerup Andreasen; Ann Taber; Kristine Young-Halvorsen; Anders Neijber; Jørgen Bjerggaard Jensen; Lars Dyrskjøt (European Urology Open Science, 2023)
Background: Transurethral resection of bladder tumor (TURBT) is a central component in the diagnosis of non–muscle-invasive bladder cancer (NMIBC) and can be guided by several optical imaging techniques for better visualization of lesions. Objective: To investigate if a change in tumor microenvironment (TME) composition could be observed as an effect of hexaminolevulinate (HAL)-assisted blue light cystoscopy (BLC) in TURBT samples from patients with bladder cancer. Design, setting, and participants: This was a retrospective study of 40 patients with bladder cancer who underwent either BLC-guided TURBT (n = 20) or white light cystoscopy (WLC)-guided TURBT (n = 20) before radical cystectomy (RC). Tissue samples (n = 80) were collected from paired TURBT and RC specimens for all 40 patients. Tumor tissue was stained using multiplex immunofluorescence and immunohistochemistry. Outcome measurements and statistical analysis: Immune cell infiltration was assessed according to the proportions of each immune cell or immune evasion marker and the relative change from TURBT as baseline was calculated. Statistical comparisons between groups were performed using the Wilcoxon rank-sum test or the paired-sample Wilcoxon test. Results and limitations: Comparison of relative changes in the TME revealed a significant decrease in stromal infiltration of cytotoxic T cells (p = 0.024), B cells (p = 0.041), and stromal cells expressing PD-1 (p = 0.011) in patients treated with BLC-guided TURBT compared to WLC-guided TURBT. Conclusions: Our pilot study showed that HAL-BLC during TURBT in bladder cancer may influence the immune cell composition and TME. Patient summary: We investigated the potential therapeutic effect of blue light versus white light for guidance in removing bladder tumors via the urethra in patients with bladder cancer. For blue light guidance, a compound called hexaminolevulinate is used to visualize tumor tissue. We found changes in immune cell composition that may have been influenced by the blue light guidance.